2015
DOI: 10.1509/jim.13.0166
|View full text |Cite
|
Sign up to set email alerts
|

Spillover of Distrust from Domestic to Imported Brands in a Crisis-Sensitized Market

Abstract: Spillover of distrust from domestic brands to foreign brands during an industry-wide scandal is an important but overlooked issue in the international marketing domain. Drawing on assimilation/contrast and attribution theories, the authors develop a general model of trust erosion in a multibrand product-harm crisis involving three brand categories: focal (domestic) brands, contrasting (imported) brands, and hybrid (manufactured domestically but with foreign brand names) brands. Assimilative associations in an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 72 publications
(129 reference statements)
1
39
0
Order By: Relevance
“…For instance, a significant effect of perceived crisis severity on Germany's microcountry image was found, with a higher level of severity being related to a less positive microcountry image (Magnusson et al, 2014). Gao et al (2015) found that the higher degree of perceived crisis severity related to a brand in a focal category; the greater the assimilation effect against noncontaminated brands in the same category, the greater will be the contrast effect favoring the contrasting category. Considering these findings, the following hypothesis is proposed:…”
Section: Perceived Severity Of a Product-harm Crisismentioning
confidence: 95%
See 3 more Smart Citations
“…For instance, a significant effect of perceived crisis severity on Germany's microcountry image was found, with a higher level of severity being related to a less positive microcountry image (Magnusson et al, 2014). Gao et al (2015) found that the higher degree of perceived crisis severity related to a brand in a focal category; the greater the assimilation effect against noncontaminated brands in the same category, the greater will be the contrast effect favoring the contrasting category. Considering these findings, the following hypothesis is proposed:…”
Section: Perceived Severity Of a Product-harm Crisismentioning
confidence: 95%
“…Gao et al. () found that the higher degree of perceived crisis severity related to a brand in a focal category; the greater the assimilation effect against noncontaminated brands in the same category, the greater will be the contrast effect favoring the contrasting category. Considering these findings, the following hypothesis is proposed:…”
Section: Hypotheses Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Although it is sometimes used interchangeably with distrust in the literature, suspicion differs from distrust in that distrust is a reached judgment, whereas suspicion is a process or state of mind that requires the consumers to seek more information and affects their attitude and purchase intention negatively (Fein 1996;Gao et al 2015). The ulterior motive often becomes salient and arouses suspicion within consumers when unexpected and inconsistent situational cues occur (Friestad and Wright 1994).…”
Section: Ulterior Motive and Consumer Suspicionmentioning
confidence: 99%